Влияние пластических покрытий на прочность частиц порошков крупнозернистого карбида вольфрама WC, полученного при температуре 2200–2300 °С - Бондаренко, В.П.; Матвейчук, А.А.; Лошак, М.Г.; Литошенко, Н.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
In work it is investigated influences of coverings from plastic metals of cobalt, nickel, copper, an alloy of cobalt with the titan on compression strength of individual particles of coarsegrained carbide of tungsten WC. The obtained data are statistically processed. It is established, that coverings from cobalt on
particles of coarse-grained carbide of tungsten WC leads to increase of their strength.